Emerging roles of PHLPP phosphatases in lung cancer - Xia, Xinhang; Pi, Wenhu; Chen, Meng; Wang, Wei; Cai, Danyang; Wang, Xuequan; Lan, Yanli; Yang, Haihua (Frontiers in Oncology, 2023)
Pleckstrin homologous domain leucine-rich repeating protein phosphatases (PHLPPs) were originally identified as protein kinase B (Akt) kinase hydrophobic motif specific phosphatases to maintain the cellular homeostasis. With the continuous expansion of PHLPPs research, imbalanced-PHLPPs were mainly found as a tumor suppressor gene of a variety of solid tumors. In this review, we simply described the history and structures of PHLPPs and summarized the recent achievements in emerging roles of PHLPPs in lung cancer by 1) the signaling pathways affected by PHLPPs including Phosphoinositide 3-kinase (PI3K)/AKT, RAS/RAF/ mitogen-activated proteinkinase kinase (MEK)/ extracellular signal-regulated kinase (ERK) and Protein kinase C (PKC) signaling cascades. 2) function of PHLPPs regulatory factor USP46 and miR-190/miR-215, 3) the potential roles of PHLPPs in disease prognosis, Epidermal growth factor receptors (EGFR)-tyrosine kinase inhibitor (TKI) resistance and DNA damage, 4) and the possible function of PHLPPs in radiotherapy, ferroptosis and inflammation response. Therefore, PHLPPs can be considered as either biomarker or prognostic marker for lung cancer treatment.